SOCIOSEMIOTIC INTERPRETATION OF POLITICAL JARGON USED BY LEGISLATIVE CANDIDATE IN 2024 GENERAL ELECTION - Manik, Sondang; Tiara Kristina Pasaribu; Erika Sinambela; Roni Arahta Sembiring; Risda Hartati Sitorus (University of Kuningan, 2025)
The phenomena of language have become a sociosemiotic issue. Many parties were joining the election. To win the election, they used attributes as a tool to campaign, such as posters, ballyhoos, and banners that hung on the side of the roads. The content of the posters included the identity and picture of the legislative candidate and the party's name, and they used political jargon. To express their identity or goal of the party, to find out the meaning of political jargon, and to understand its sociosemiotic interpretation. By using the descriptive qualitative method. Using Halliday's and Pterce’s theories, the result is that political jargon has a deep meaning and sociosemiotic interpretation. The heuristic function is not found in the function of language analysis in political jargon. Still, it was found that the interactional and personal functions are dominantly used in political jargon. Semiotic meaning found in political jargon that expresses the meaning of color, dress cr logo used in political jargon Sociosemiotic interpretation used in political jargon, that comes from sociolinguistics analysis, and Semiotic analysis Keywords: Sociosemiotic Interpretation, Political Jargon